Detection of hydrogen peroxide releasing from prostate cancer cell using a biosensor - Crulhas, Bruno P. [UNESP]; Ramos, Naira P. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (Springer, 2016)
In this work, highly sensitive and selective hydrogel microstructures to detect hydrogen peroxide releasing from cancer cell based on electrochemical biosensors are proposed. Gold nanoparticles (AuNPs) were conjugated with horseradish peroxidase and were dispersed in the prepolymer solution of poly(ethylene glycol) diacrylate. The prepolymer solution was photolithographically patterned in alignment with an array of Au microelectrodes fabricated on glass. Performance of this biosensor was characterized by transmission electron microscopy, electrochemical impedance spectroscopy, and cyclic voltammetry. Under the optimal condition, the proposed biosensor can detect hydrogen peroxide (H2O2) in a wide linear range from 2 to 100 mu M with a low detection limit of 0.01 mu M. It can be also directly used to mark out extracellular H2O2 released from prostate cells. Furthermore, the reproducibility, stability, and selectivity of the biosensor are analogous with the previous report, so this methodology can be used in physiological and pathological detection of H2O2 in the future.